The effectiveness of psycho education towards depression, anxiety and stress level of patients with pulmonary tuberculosis - Suryani, Suryani; Widianti, Efri; Widianti, Efri; Hernawati, Taty; Hernawati, Taty; Sriati, Aat; Sriati, Aat (Universitas Airlangga, 2016)
Pulmonery Tuberculosis is a chronic pulmonary disease that affects physicallly and psychosocially for the patients . Until now, the governmentâs programs in overcoming this disesase still focus on treatment and prevention of infection. The programs has not yet to lead to a psychosocial problem of the patients whereas the psychosocial impact has a big influence on treatment compliance and prognosis of patients with Pulmonery Tuberculosis. This study was quassy experiment to test the effect of psychoeducation on the level of stress, anxiety and depression of Patients with pulmonary tuberculosis. 74 patients with Pulmonery Tuberculosis involved in this study divided into two group (37 involved in intervention and 37 involved as control group). The result of the study showed that psychoeducation was effective in reducing stress, anxiety and depression of the patients with Pulmonery Tuberculosis. Psycho education should be provided for patients with pulmonary tuberculosis at the Community health Center.Â Â Keywords: Â Â intervention, psychoeducation, pulmonary tuberculosis, Â Â Â Â